2005
DOI: 10.1002/jcb.20253
|View full text |Cite
|
Sign up to set email alerts
|

?-Catenin and BMP-2 synergize to promote osteoblast differentiation and new bone formation

Abstract: Mutations of critical components of the Wnt pathway profoundly affect skeletal development and maintenance, probably via modulation of β-catenin signaling. We tested the hypothesis that β-catenin is involved in mesenchymal lineage allocation to osteogenic cells using a β-catenin mutant with constitutive transcriptional activity (ΔN151). Although this stable β-catenin had no effects by itself on osteogenic differentiation of multipotent embryonic cell lines, it synergized with bone morphogenetic protein-2 (BMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 41 publications
5
155
1
4
Order By: Relevance
“…It was shown that stable β-catenin is able to induce ALP activity in C3H10T1/2 cells by transient transfection [53], enhance osteoblastogenesis (by retroviral infection) in both C3H10T1/2 and ST2 cells [89], and dramatically stimulate osteoblastogenesis by synergizing with BMP-2 in C3H10T1/2 cells via retroviral infection [92]. A study showed that retroviral expression of a stabilized form of β-catenin in C3H10T1/2 cells induced expression of ALP mRNA and protein (but not osteocalcin expression) in non-differentiated medium [93].…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that stable β-catenin is able to induce ALP activity in C3H10T1/2 cells by transient transfection [53], enhance osteoblastogenesis (by retroviral infection) in both C3H10T1/2 and ST2 cells [89], and dramatically stimulate osteoblastogenesis by synergizing with BMP-2 in C3H10T1/2 cells via retroviral infection [92]. A study showed that retroviral expression of a stabilized form of β-catenin in C3H10T1/2 cells induced expression of ALP mRNA and protein (but not osteocalcin expression) in non-differentiated medium [93].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…A study showed that retroviral expression of a stabilized form of β-catenin in C3H10T1/2 cells induced expression of ALP mRNA and protein (but not osteocalcin expression) in non-differentiated medium [93]. Another study showed that constitutively active β-catenin has no effect on basal ALP activity in either C3H10T1/2 or C2C12 cells [92]. Deletion of β-catenin by using adenovirus expressing the Cre recombinase in calvarial osteoblasts resulted in delayed and diminished expression of osteocalcin as well as in significantly reduced mineralization [94].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…To address this issue, this work aimed to study the stability of two of the most commonly used housekeeping genes in osteogenic differentiation studies of stem cells: ACTB and GAPDH (Vandesompele et al 2002;Cho et al 2005;Mbalaviele et al 2005), in hBMSCs undergoing osteogenic differentiation. The results were compared with the stability of the gene ribosomal protein L13A (RPL13A), which has been shown to have stable expression levels in bone marrow tissues (Vandesompele et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…EGF and TGF␤ synergize to regulate several important cellular processes, including colony formation in soft agar (24), the epithelial to mesenchymal transition (25), and cell movement during tissue remodeling (26). The ability to tightly control gene expression by the synergistic interaction of extracellular regulators, such as growth factors, is likely to be an important aspect of gene regulation in vivo and has already been demonstrated for some systems (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%